2021
DOI: 10.47176/mjiri.35.85
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between the severity of coronary artery disease and inflammatory factors of ‎MHR, PHR, NHR, and IL-25

Abstract: Background role of inflamm disease and inf (NHR), and IL Methods: In Farshchian hea 25 were measu history of hype Statistical anal multiple linear Results: The Gensini score ( hypertension, h Conclusion: coronary artery profiles, predic patients prone t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“… 19 Despite this, three studies showed no significant differences between the two patient groups. 6 , 7 , 12 …”
Section: Patient Historymentioning
confidence: 99%
“… 19 Despite this, three studies showed no significant differences between the two patient groups. 6 , 7 , 12 …”
Section: Patient Historymentioning
confidence: 99%
“…Due to the inextricable interaction between platelet and HDL-C in the pathogenesis of atherosclerosis, we contemplated that their combination indices would have great clinical significance for improving cardiovascular risk prediction, and should be the subject of intensive investigations both in humans and in animal models. A recent study observes that PLT/HDL-C ratio (PHR) is considered an independent variable for the prediction of the Gensini score in patients with an initial diagnosis of CHD ( 19 ). Another study demonstrates that PHR is significantly increased in patients with nascent metabolic syndrome (MetS) and appears to be a valid biomarker of MetS.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Standard laboratory procedures for quality control were strictly followed. 9–11 , 13 Leukocyte-derived ratios were defined as follows: NLR= NE/LYM, dNLR= NE /[WBC-NE], MLR= MO/LYM, PLR= PLT/LYM, WMR= leukocyte/mean PLT volume, MNM= LYM × NE/10 4 , SIRI= NE × MO/LYM, and SII = PLT/NE/LYM.…”
Section: Methodsmentioning
confidence: 99%
“…19 Standard laboratory procedures for quality control were strictly followed. [9][10][11]13 Leukocyte-derived ratios were defined Hospital professionals also measured the color Doppler ultrasound of the carotid artery after the patient was rested in a supine position for approximately 15 min. Bilateral common carotid arteries, bifurcation, and the internal and external carotid arteries were scanned along the direction of the blood vessels to determine the intima-media thickness (IMT).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation